2021
DOI: 10.1038/s41541-020-00266-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduced immune responses to hepatitis B primary vaccination in obese individuals with nonalcoholic fatty liver disease (NAFLD)

Abstract: Obesity and cirrhosis are associated with poor hepatitis B virus (HBV) vaccine responses, but vaccine efficacy has not been assessed in nonalcoholic fatty liver disease (NAFLD). Sixty-eight HBV-naïve adults with NAFLD were enrolled through the Canadian HBV network and completed three-dose HBV or HBV/HAV vaccine (Engerix-B®, or Twinrix®, GlaxoSmithKline). Anti-HBs titers were measured at 1–3 months post third dose. In 31/68 subjects enrolled at the coordinating-site, T-cell proliferation and follicular T-helper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…During the COVID-19 pandemic, associations with severe disease were diligently recorded, and obesity emerged as an independent risk factor [15,[18][19][20], which mirrors findings from the 2009 H1N1 influenza pandemic [69][70][71][72][73][74]. Furthermore, patients living with obesity have reduced antibody production in response to vaccination, including influenza and hepatitis B [69,[75][76][77][78]. The causes for this paradoxical state of chronic inflammation but reduced adaptive responses to novel antigens in obese individuals remain elusive, however, this is likely due, at least in part, to the drastic alterations in the B cell compartment described above.…”
Section: Impact Of Obesity On the Response To Infection And Vaccinati...mentioning
confidence: 65%
“…During the COVID-19 pandemic, associations with severe disease were diligently recorded, and obesity emerged as an independent risk factor [15,[18][19][20], which mirrors findings from the 2009 H1N1 influenza pandemic [69][70][71][72][73][74]. Furthermore, patients living with obesity have reduced antibody production in response to vaccination, including influenza and hepatitis B [69,[75][76][77][78]. The causes for this paradoxical state of chronic inflammation but reduced adaptive responses to novel antigens in obese individuals remain elusive, however, this is likely due, at least in part, to the drastic alterations in the B cell compartment described above.…”
Section: Impact Of Obesity On the Response To Infection And Vaccinati...mentioning
confidence: 65%
“…In addition to the immune T cells mentioned above, follicular helper CD4 + T cells (TFH cells) and the molecules secreted by TFH cells provide help to B cells in humoral immunity [177]. However, pTFH cells response in MAFLD patients with BMI > 35 and BMI < 35 at baseline and postvaccination was no difference [178]. Therefore, the function of TFH cells is still to be explored in MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of BMI on the effectiveness of vaccinations has long been a cause for investigation; most studies concern the hepatitis B vaccine. The rather large literature relating to the immune response to the hepatitis B vaccine and BMI is almost solely oriented on the existence of this relationship [ 5 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], while critical voices are rather isolated [ 37 , 38 ]. A recent study has indicated the involvement of leptin as crucial in the immunogenicity of the HBV vaccine [ 33 ].…”
Section: Discussionmentioning
confidence: 99%